Electing the Australian Senate: evaluating the 2016 reforms. (4th May 2018) - McAllister, Ian; Muller, Damon
ABSTRACT: The Australian Senate is one of the most powerful upper houses in the world, so the design of its electoral system is unusually important. The 2013 Senate election saw the highest non-major party vote since the introduction of proportional representation in 1949. Several of the minor party and independent candidates that were elected won miniscule proportions of the first preference vote, highlighting the widespread use of sophisticated 'vote harvesting' co-ordinated by party strategists. To address this problem, the Senate electoral system was changed in 2016 to abolish group voting tickets and replace it with preferential voting above the line. This paper traces the debates leading up to the 2016 reform, the reasons for it and evaluates how voters adapted to the new system.